2016
DOI: 10.1038/nchem.2622
|View full text |Cite
|
Sign up to set email alerts
|

Ballbot-type motion of N-heterocyclic carbenes on gold surfaces

Abstract: Recently, N-heterocyclic carbenes (NHCs) were introduced as alternative anchors for surface modifications and so offered many attractive features, which might render them superior to thiol-based systems. However, little effort has been made to investigate the self-organization process of NHCs on surfaces, an important aspect for the formation of self-assembled monolayers (SAMs), which requires molecular mobility. Based on investigations with scanning tunnelling microscopy and first-principles calculations, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
250
1
19

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 215 publications
(297 citation statements)
references
References 33 publications
22
250
1
19
Order By: Relevance
“…However, the 730 cm −1 peak was not suppressed; therefore, the spectrum reflects the coexistence of upright and flat‐lying species. Such behavior is not uncommon ‐a similar interpretation was proposed for the coverage‐dependence of benzoic acid adsorption on Cu(110) …”
Section: Figuresupporting
confidence: 61%
See 3 more Smart Citations
“…However, the 730 cm −1 peak was not suppressed; therefore, the spectrum reflects the coexistence of upright and flat‐lying species. Such behavior is not uncommon ‐a similar interpretation was proposed for the coverage‐dependence of benzoic acid adsorption on Cu(110) …”
Section: Figuresupporting
confidence: 61%
“…Recently, N ‐heterocyclic carbenes (NHCs) have emerged as promising alternatives to thiols for the formation of robust, ordered SAMs on Au . Seminal work by Siemeling and Johnson showed that NHCs bind to planar Au surfaces.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The surface energy of Pd is higher compared to Au, so that the rearrangement would be thermodynamically favored . The trigger for the reconstruction process could be the binding of the NHC, which is known to form adatoms on Au surfaces . A similar behavior on the alloy NPs would lead to a pulling of Au atoms to the surface and would explain the Au enrichment determined by surface sensitive TXRF.…”
Section: Resultsmentioning
confidence: 99%